U.S. environmental policy and politics a documentary history - Hillstrom, Kevin 1963-.; Gale Group (Washington, D.C. CQ Press, 2010)
Explores the many ways throughout American history in which environmental concerns have intersected with issues of energy production and consumption, government regulation, private property rights, economic growth, and lifestyle choices.
Seizing land and riches in the New World (1600-1800) -- An emerging empire (1800-1850) -- Conservation gains in an era of frontier conquest (1850-1900) -- Theodore Roosevelt and the Age of Conservation (1900-1920) -- Environmental health in the industrial city (1800-1920) -- Environmental policy-making during the New Deal (1920-1940) -- Environmental politics in the Age of Suburbanization (1940-1960) -- The "golden age" of environmental legislation (1960-1980) -- Public health and environmental regulation (1980-present) -- Conservation and land use (1980-present) -- Energy policy and global climate change.
Electronic reproduction.
Keywords: Environmental policy -- History -- United States -- Sources; Environmental policy -- History. -- United States; Environmentalism -- History -- United States -- Sources; Environmentalism -- History. -- United States; Electronic books